Fred Donner, Early Islamic Narratives and The Problem of The Authenticity of The Qur’an - Saad, Mukhlisin (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This article examines Fred Donner’s argumentation in criticizing the revisionists group in the discourse of Qur’anic studies. By textual and content analysis, this article argues that Fred Donner is of the view that the Qur’an was completed as a corpus at the time of the Prophet Muhammad. Donner’s argument is based on a comparative study between the Qur’an and the corpus that emerged about two centuries after the prophet Muhammad. Among the Islamic sources that became the object of his comparative study were the hadith and prophetic history. Based on his findings, that the Qur’an, in some degree, has different tone of elaboration on the political leadership. While the hadith speaks more about leadership with many terminologies, and even describes the names of companion, the Qur’an is silent on the issue of leadership with little reference on it. This, according to Donner, becomes proof that the Qur’an came before the hadith. And it is also certain that the Qur’an became a fixed corpus during the lifetime of the Prophet Muhammad. Donner’s argumentation with this method of comparing hadith implies the idea that hadith came later.